Freezing of equine semen under two schemes of addition of dimethylformamide - Pérez Q., Daniel Domingo (2017)
The aim of this study was to evaluate the post-thawing quality of equine semen subjected to two dimethylformamide (DMF) addition schemes during freezing. Semen of five Colombian Creole horses was obtained and diluted in modified INRA82® medium with two DMF addition treatments, T1: immediate addition of 5% DMF, and T2: fractional addition of 5% DMF (during 10 min). Semen was packed into 05. ml straws and subjected to conventional freezing. Sperm motility, vitality and morphology before and after dilution were assessed. In addition, a post-thaw analysis of sperm motility and kinetics using a computerized system and the evaluation of plasma membrane integrity by the hypoosmotic test (HOS) were performed. Before and after freezing, a lower reduction in sperm motility was observed by the immediate addition of DMF (T1), compared to the fractional addition of the cryoprotectant (T2) (p<0.05). Superior values of total and progressive post-thaw motility for T1 were found, while the straightness index (STR) was higher for T2 (p<0.05). It is concluded that the immediate addition of DMF during freezing provides a better protection of the post-thawing sperm motility of stallion semen than the fractional addition of this cryoprotectant.